The Role of High Mobility Group Box 1 Protein (HMGB1) in the Immunopathology of Experimental Pulmonary Tuberculosis - Hernández-Pando, Rogelio (2015)
Fil: Fil: Bottasso, Oscar. Institute of Experimental and Clinic Immunology, Rosario, IDICER, CONICET, School of Medical Sciences. UNR. Rosario; Argentina